Upaya Hukum Kredit Bermasalah Bagi Bank Di Masa Pandemi Covid-19 - Saddam Hussein Ramadhan; Yanuar Fitra Firdaus; David Brilian Sunlaydi; Rexy Mierkhahani (Jurnal USM Law Review)
his study aims to examine whether the Covid-19 Pandemic can be classified as Force Majeure or not and how legal remedies can be taken by the Bank as a creditor in order to protect their rights to obtain credit from customers as debtors whose urgency in this research is to provide information regarding protection measures. as well as legal protection for creditors who have failed to pay during the Covid-19 pandemic. The legal research method used is normative legal research by conducting studies through the Statute Approach and Conceptual Approach. The results of this study reveal that efforts that can be made by banks to resolve non-performing loans are to make efforts for non-performing loans through a credit restructuring scheme by considering the criteria for debtors who are eligible for a credit restructuring policy.